Mitigating temporal mismatches in forensic soil microbial profiles. Issue 6 (2nd November 2019) - Pasternak, Zohar; Luchibia, Aineah Obed; Matan, Ofra; Dawson, Lorna; Gafny, Ron; Shpitzen, Moshe; Avraham, Shlomit; Jurkevitch, Edouard
ABSTRACT: Forensic implementation of soil bacterial DNA profiling is limited by the potential for temporal mismatch of DNA profiles, e.g. after storage or seasonal changes. We compared profiles of samples retrieved at one location over 14 years after air-drying, freeze-drying and –80 °C freezing storage. Sample mismatch in freeze-dried and air-dried samples was significant after two years and continued to increase yearly, whereas profiles after –80 °C freezing remained unchanged for many years. In an attempt to mitigate inter-seasonal temporal mismatches, e.g. when months pass between crime and seizure of evidence, soils sampled in winter and summer were exposed to artificial 'summer' and 'winter' conditions, respectively, and their DNA profiles were compared. Differences were small between soil types, larger between seasons and largest between 'natural' and 'artificial' seasons. Understanding sources of temporal variations is critical for storage of forensics samples and for developing mitigation procedures that could help overcome these time-induced limitations.